CORRELATIONS BETWEEN SURFACE-WATER CHARACTERISTICS AND GEOLOGICAL SUBSTRATUM IN AGHIRES MINING AREA, ROMANIA - V. MĂCICĂŞAN; Gh. ROŞIAN; O.-L. MUNTEAN; R. MIHĂIESCU (Aerul şi Apa: Componente ale Mediului, 2013)
The exploitation activities from Aghireş generated a series of lakes, drainage ditches and creeks, specific for mining. In this paper, the physical and chemical parameters of the mining lakes are presented, the results being then correlated with the characteristics of the geological substratum. For the physico-chemical testing, three different water samples have been collected for each of the ten mining lakes. The samples where then analyzed in the field, by using a portable multi-parameter measuring instrument. The final results confirm the initial premise that the water quality is influenced by the geological substratum. The parameters that stand out the most are the pH, electric conductivity, and salinity, which vary quite significantly between the collected samples. The pH parameter is the most illustrative in this respect, given that three of the mining lakes have an extremely acidic water environment (with pH levels lower than 4.0), while the rest of the lakes have neutral pH levels. This difference can be explained by the presence of pyrite, associated with coal deposits in the underlying formations of acidic lakes.